Consumer animosity, conspicuous consumption and solidarity as antecedents of boycott in Malaysia - Mohamed Ghazali, Raimi Nur Hakimi (2019)
This study addresses the consumer boycott phenomena in Malaysia. It examines the influences of Consumer Animosity, Conspicuous Consumption, and Solidarity on the decision to boycott; and to discover how Consumer Power moderates the decision to boycott. Using Social Cognitive Theory as the underpinning theory, this study proposes a conceptual framework that focuses on the relationship of: (i) Consumer Animosity on boycott, (ii) Conspicuous Consumption on boycott, (iii) Solidarity on boycott, and (iv) the moderating role of Consumer Power on the relationship between the exogenous and endogenous variables. Questionnaires were distributed to Malaysian consumers aged 18 and above. Online respondents were collected by utilising convenience sampling technique, while offline respondents were collected by employing snowballing sampling technique. Ultimately, 254 questionnaires were usable for data analysis. In this study, Variance Based-Structural Equation Modelling (VB-SEM) was used to analyse the data (SmartPLS 3.0). Our analysis reveals that all the exogenous constructs have positive relationships with the endogenous construct. In particular, solidarity – as a newly proposed construct – has a positive relationship with boycott. However, the relationships of the moderating factor showed non-significant results. In conclusion, drawing from the findings of this study, the boycott literature is extended by the result of the positive relationship between solidarity and boycott. This has also extends Social Cognitive Theory because it expands the existing knowledge and offers new insight. Practically, managers and marketers are able to strategize their marketing plans better so as to avoid consumers from boycotting their products and/or organisation.